SINTESIS DAN KARAKTERISASI SENYAWA ION Mg(OH)2 DENGAN METODE PENGENDAPAN - Nurul Ilma Pohan, Nadiya; Sakinahdyah Harahap, Balqis; Krisdayanti Purba, Hendike; Maida Aritonang, Tiur; Siti Jahro, Iis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to synthesize and characterize magnesium hydroxide (Mg(OH)₂) using the precipitation method. The experiment was conducted by reacting magnesium chloride (MgCl₂) and sodium hydroxide (NaOH) solutions under controlled laboratory conditions. The synthesis produced a white precipitate of Mg(OH)₂ with a mass of 1.60 grams after filtration, washing, and drying. Characterization included physical observation, solubility testing, and pH measurement. The results showed that Mg(OH)₂ is a white solid with low solubility in water but dissolves in hydrochloric acid (HCl) due to neutralization reactions. The measured pH was around 9, indicating that Mg(OH)₂ is a weak base. These findings are consistent with theoretical concepts of ionic compounds, solubility equilibrium, and precipitation reactions. Therefore, the precipitation method is effective for synthesizing Mg(OH)₂ and supports the relationship between theoretical and experimental understanding in inorganic chemistry.